Tinjauan Literatur Analisis Uji R Berganda dan Uji Lanjut dalam Statistik Inferensial pada Penelitian Pendidikan Jasmani - Pinton Setya Mustafa (Peneliti.net, 2023)
The purpose of this article is to discuss the multiple R test and further tests on inferential statistics used in physical education. Analysis of the multiple R test and further tests were carried out in a correlational research design. The study design was conducted to reveal the relationship between the independent variable (X) and the dependent variable (Y). In that study, of course, also revealed more than one independent variable (X1, X2, X3, ...) and the dependent variable (Y). This research is a type of library research with research procedures: typifying, collecting references, and analyzing the literature. So in analyzing correlational research of more than two variables using the R test analysis and further tests. In physical education correlational research can also be done to uncover various factors that can be related to physical activity. Thus as a student or researcher who wishes to conduct correlational research if more than one independent variable can use multiple R test analysis and follow-up tests with the F test.